PELAKSANAAN BESTUURS PLAN DI DESA CITRADAMAI KECAMATAN RANGSANG KABUPATEN KEPULAUAN MERANTI TAHUN 2013-2018 - Roziqin, Khoirur; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The implementation of the Bestuurs Plan in Citradamai Village in 2013-2018 is still not in accordance with what was planned. This is due to the lack of public participation and a lack of budget funds. The purpose of this study is to see the implementation of the Bestuurs Plan in Citradamai Village, Rangsang District, Meranti Islands Regency in 2013-2018. And to find out what are the obstacles of the Citradamai Village Government in implementing the 2013-2018 Bestuurs Plan. This research uses qualitative methods with descriptive analysis case studies. Data collection techniques with interviews as primary data and literature study as secondary data        The theoretical concept used by the researcher is the Bestuurs Plan which has indicators in four basic stages of planning, namely: setting goals, formulating the current situation, identifying supporting and inhibiting factors towards goals and formulating steps to achieve goals. This research uses qualitative research methods, with descriptive data review. In collecting data, researchers used interview and documentation techniques.                   The results of this study indicate that the implementation of the Bestuurs Plan in Citradamai Village, Kepulauan Meranti Regency in 2013-2018 is still ineffective. This can be seen from the large number of development plans in Citradamai Village that are still not realized and even not realized at all compared to other villages in Rangsang District. In addition, the obstacle is not yet optimal in the performance of the Citradamai Village government because Citradamai Village is an pemkaran village, this causes the implementation of the Bestuurs Plan in Citradamai Village not according to what was desired. Keywords: Bestuurs Plan, Implementation, Planning Stages